(untitled) (Asian Journal of Medical and Biological Research, 2016)
The research work was conducted for induced breeding of Vietnames Koi (Anabas testudineus) using carpPG extract and Ovaprim hormone at Tasty Fish and Feeds Industries Limited, Melandah, Jamalpur during March to May, 2015. Brood fishes were reared for 4-5 months in the brood rearing pond by providing farm-made artificial feed (containing 32% protein) for maturation before onset of breeding season. Two different hormones i.e., PG-PG (both for male and female), and PG-Ovaprim (PG for male and Ovaprim for female) were used as inducing agents for the purpose of induction of breeding A. testudineus. The broods were induced with PG-PG hormone at the doses of 2 mg PG/Kg body weight of male and 7 mg PG/Kg body weight of female and PG-Ovaprim hormone were used at the doses of 2 mg PG/Kg body weight of male and 7 ml Ovaprim/Kg body weight of female and designated as treatments T1 and T2, respectively. Ovulation rates (100%) were similar in both the treatments, whereas, fertilization, hatching, and survival rates were 78.11±3.24%, 70.22±3.40%, and 51.22±3.96% in T1 and 71.00±3.97%, 60.89±4.20%, and 48.89±4.41% in T2, respectively. Although comparatively better breeding performance was found for carp PG extract but these values were not significantly higher compared to Ovaprim. Therefore, comparing the breeding performance and considering the cost-benefit analysis it is suggested that Ovaprim could be used as an alternative of carp PG extract for the induced breeding of Vietnames koi. Asian J. Med. Biol. Res. December 2015, 1(3): 607-611